2011
DOI: 10.1037/a0024469
|View full text |Cite
|
Sign up to set email alerts
|

The impact of child parent relationship therapy on child behavior and parent-child relationships: An examination of parental divorce.

Abstract: The current study used a mixed methodological approach to examine the impact of Child-Parent-Relationship Therapy (CPRT) on divorced parents and their children. Specifically, in the present study, the authors investigated parents' perceptions of the impact of CPRT on the parent, the child, and the parent–child relationship. CPRT was found to be helpful in reducing parenting stress and child behavior problems. Parents also reported that CPRT helped them feel more connected to their children and provided them wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…When comparing those who experienced divorce before the age of twelve with those who experienced divorce after the age of twelve, there were no differences in terms of attachment, couple satisfaction, parental regard, and depression, anxiety and stress. This is surprising due to previous findings from a number of studies that found there is a difference (Amato & Afifi 2006;Bojuwoye, & Akpan, 2009;Dillman, Purswell, Lindo, Jayne, & Fernando, 2011;Kelly & Emery 2003;Mustonen, Huurre, Kiviruusu, Haukkala, & Aro, 2011;Somody, & Hobbs, 2006;Undheim, 2005;Wallerstein, & Lewis, 2007). However, the differences may be in other areas other than attachment, couple satisfaction, parental regard, and depression, anxiety and stress.…”
Section: Chapter 4: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When comparing those who experienced divorce before the age of twelve with those who experienced divorce after the age of twelve, there were no differences in terms of attachment, couple satisfaction, parental regard, and depression, anxiety and stress. This is surprising due to previous findings from a number of studies that found there is a difference (Amato & Afifi 2006;Bojuwoye, & Akpan, 2009;Dillman, Purswell, Lindo, Jayne, & Fernando, 2011;Kelly & Emery 2003;Mustonen, Huurre, Kiviruusu, Haukkala, & Aro, 2011;Somody, & Hobbs, 2006;Undheim, 2005;Wallerstein, & Lewis, 2007). However, the differences may be in other areas other than attachment, couple satisfaction, parental regard, and depression, anxiety and stress.…”
Section: Chapter 4: Discussionmentioning
confidence: 88%
“…Some risk factors that mental health practitioners should look for include the intensity of the divorce, level of family conflict before and/or after the divorce, parental involvement and closeness, the client's beliefs about expectations surrounding a relationship (Dillman et al, 2011;Kelly & Emery, 2003;Mahl, 2001;Morrison, 2014;Stanley-Hagan & Hetherington 1999;Wallerstein & Lewis, 2007,Whiteside, 1998. Clinicians can ask, "How did your parents navigate their divorce?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When parents are separating, they may be distracted and become emotionally and physically unavailable to their children (Sutherland et al, 2012). It was reported by Taylor et al (2011) that in times of trauma, some individuals become egocentric and fail to think of the needs of their children which also can add stress to the household. A divorce can be just one indicator of more underlying familial problems that need to be addressed (Huurre, Junkkari, & Aro, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have noted the success of CPRT to treat a variety of problems. Specifically, researchers have noted decreases in externalizing and internalizing behavior problems (Kidron & Landreth, 2010;Landreth & Bratton, 2006), greater child adaptability, leadership, and social behavior (Post, McCallister, Shelly, Hess, & Flowers, 2004), improved academic success (Landreth & Bratton, 2006); and improved parental acceptance of children and decreased parenting stress (Dillman, Purswell, Lindo, Jayne, & Fernando, 2011;Bratton & Landreth, 1995). CPRT also appears to have long--lasting effects.…”
mentioning
confidence: 99%